1992
DOI: 10.1111/j.1476-5381.1992.tb14352.x
|View full text |Cite
|
Sign up to set email alerts
|

Study of mechanisms of glucocorticoid hypertension in rats: endothelial related changes and their amelioration by dietary fish oils

Abstract: 1 To investigate possible mechanisms of increased systolic blood pressure after 1 weeks treatment with dexamethasone and its amelioration by fish oil feeding, we have examined the reactivity of aortic rings and perfused mesenteric resistance vessels. 2 Thirty six Sprague-Dawley rats were initially divided into two groups and fed a semisynthetic diet containing either (10% by weight) hydrogenated coconut oil and safflower oil mixture (HCO/S) (24 rats) or fish oil (12 rats) for 5 weeks. From the end of the fourt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
2

Year Published

1994
1994
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 37 publications
2
13
2
Order By: Relevance
“…The favourable effects of DHA on vasoreactivity 10 are most likely attributable to direct and indirect effects of DHA on the arterial wall and may include DHA incorporation into endothelial membranes increasing membrane fluidity, calcium influx and endogenous synthesis and release of NO. Docosahexaenoic acid could also have direct effects on receptor‐stimulated NO release, enhanced release of vasodilator prostanoids and/or endothelial‐derived hyperpolarizing factor, consistent with experimental evidence 59 . The enhanced response to sodium nitroprusside may relate to increased biotransformation to NO or increased reactivity of smooth muscle cells to vasorelaxation as a result of decreased calcium influx 60 .…”
Section: Antihypertensive Effect Of Epa Versus Dhasupporting
confidence: 60%
“…The favourable effects of DHA on vasoreactivity 10 are most likely attributable to direct and indirect effects of DHA on the arterial wall and may include DHA incorporation into endothelial membranes increasing membrane fluidity, calcium influx and endogenous synthesis and release of NO. Docosahexaenoic acid could also have direct effects on receptor‐stimulated NO release, enhanced release of vasodilator prostanoids and/or endothelial‐derived hyperpolarizing factor, consistent with experimental evidence 59 . The enhanced response to sodium nitroprusside may relate to increased biotransformation to NO or increased reactivity of smooth muscle cells to vasorelaxation as a result of decreased calcium influx 60 .…”
Section: Antihypertensive Effect Of Epa Versus Dhasupporting
confidence: 60%
“…The in vivo relevance of this effect at the relatively .low maintenance doses employed in our patients may be marginal (20). With regard to corticosteroids, Yin et al (21 ) have demonstrated that ACh-induced endothelium-dependent vasodilation is impaired in rats treated with dexamethasone, and Altura (22) has also found impaired vasodilator responses to bradykinin in rats treated with glucocorticoids. In addition, eNOS activity is not affected by glucocorticoids (23,24) and expression of iNOS can be prevented by steroids (24).…”
Section: Discussionmentioning
confidence: 94%
“…Statins have been reported to upregulate eNOS expression, reduce endothelin‐1 expression, downregulate angiotensin II AT 1 receptor expression and inhibit NAD(P)H oxidase activity 8,9 . Inhibition of NO synthesis, thereby inhibiting the vasodilator action of NO, has been suggested as one of the mechanisms responsible for the induction of hypertension by Dex in rats 10 . Atorvastatin (Ato) normalized aortic eNOS activity and systolic blood pressure (SBP) and concomitantly reduced oxidant stress in Dahl‐salt rats 11 .…”
Section: Introductionmentioning
confidence: 99%